(untitled) (Journal of the College of Basic Education, 2024)
The researcher noticed that there is a weakness in the performance of the students of the Department of Art Education in musical skills, especially after the exploratory study he conducted on a sample of the department’s students - the third stage - the morning study who are studying the subject of musical appreciation. He asked a set of questions about the aforementioned subject with the aim of identifying the students’ levels in... Concerning musical skills (listening, reading, notation, and rhythm), which revealed the need for students to develop and raise their academic performance and overcome learning difficulties by developing their musical skills. The researcher tried, using his academic experience as a graduate of the Institute of Fine Arts - Department of Music and as a teacher of art education in the General Directorate of Education in Baghdad / Al-Karkh II, in addition to his knowledge of the specialized literature and previous studie To provide effective educational content for the subject of musical appreciation in accordance with modern learning theories. Therefore, he used the Kohlberg model, which belongs to the theory of moral development and is one of the advanced and effective models in helping students to stimulate their motivation and enable them to participate in creating the appropriate teaching situation as it works to motivate students. Developing their mental and artistic abilities, and training them to choose appropriate musical content and taste it, as well as the ability to make sound taste judgments and diagnose what is desired, as the nature of musical products, including phrases and pieces It cannot be perceived by listening only or relying on mere feeling and emotion. It is necessary to consciously listen to it, interact with it, try to understand it, decipher its symbols, and assimilate its vocabulary and names according to its system of rules and theoretical and applied foundations